Chest Pain in the Emergency Department: A Critical Narrative Review of Diagnostic Strategies, Risk Stratification and Unresolved Evidence Gaps - Domina Petric (Journal of Medicine and Health Research, 2026)
Chest pain remains one of the most frequent reasons for attendance at emergency departments worldwide, and the diagnostic task it presents is unusually asymmetric: a small proportion of patients harbour an immediately life-threatening condition, while the majority have benign or self-limiting causes that nonetheless consume substantial diagnostic resources. The past decade has transformed the evidence base. High-sensitivity cardiac troponin assays, rapid serial-sampling algorithms, structured clinical decision pathways, early coronary computed tomography angiography and, more recently, machine-learning decision support have all been evaluated in large cohorts and randomised trials. This critical narrative review examines how far that transformation has improved patient-relevant outcomes rather than diagnostic process measures alone. Literature was identified through structured searching of a biomedical bibliographic index and a scholarly metadata registry, with citation-based supplementation, and appraised for design adequacy, spectrum representativeness, outcome definition and reproducibility. The synthesis identifies a consistent pattern: analytical and diagnostic performance has improved markedly, yet randomised evidence repeatedly shows neutral effects on death and recurrent infarction, and a persistent gap separates rule-out efficiency from therapeutic benefit. Performance of validated algorithms degrades in renal impairment, older age, very early presentation and among women assessed against undifferentiated thresholds. Structured pathways demonstrate favourable safety in observational validation but heterogeneous adherence in practice, and the definition of an acceptable missed-event threshold remains a value judgement rather than an empirical finding. Conditions outside the acute coronary syndrome framework, including acute aortic syndromes, pulmonary embolism, myocardial infarction with non-obstructive coronary arteries and non-cardiac causes, remain comparatively neglected in pathway design and in follow-up provision. Equity gaps in triage, testing and treatment persist across sex, ethnicity, language and health-system context. Priority research needs include outcome-anchored trials of rule-out strategies, prospective evaluation of computational decision support in routine practice, and evidence generation in settings where troponin testing and advanced imaging are not universally available.